Influence of aquatic macrophytes on the interactions among aquatic organisms in shallow wetlands (Upo Wetland, South Korea) - Keon-Young Jeong; Jong-Yun Choi; Kwang-Seuk Jeong (Journal of Ecology and Environment)
Seasonal monitoring was implemented to understand the influence of macrophyte bed structure on the composition and trophic interaction of aquatic organisms (algae, zooplankton, macro-invertebrate, and fish) in a shallow wetland (Upo Wetland, South Korea). Distinct division of the plant assemblage (reed zone and mixed plant zone) was observed. The reed zone was composed solely of Phragmites communis, whereas the mixed plant zone comprised a diverse macrophyte assemblage (Salvinia natans, Spirodela polyrhiza, Trapa japonica, Ceratophyllum demersum, and Hydrilla verticillata). Most of the aquatic organisms were more abundant in the mixed plant zone than in the reed zone, and this was positively associated with the seasonal development of macrophyte cover. Stable isotope analysis showed seasonal interactions among aquatic organisms. The majority of aquatic animal (zooplankton, Odonata, and Ephemeroptera) were dependent on epiphytic particulate organic matter (EPOM), and the dependence on EPOM gradually increased toward autumn. Interestingly, Lepomis macrochirus consumed Ephemeroptera and zooplankton in both macrophyte zones, but Micropterus salmoides depended on different food items in the reed zone and the mixed plant zone. Although, M. salmoides in the reed zone showed food utilization similar to L. macrochirus, it consumed Odonata or small L. macrochirus in the mixed plant zone. Based on these results, it appears that differences in the structure of the two macrophyte zones support different assemblages of aquatic organisms, strongly influencing the trophic interactions between the aquatic organisms.